Significant role of biomass burning in heavy haze formation in Nanjing, a megacity in China: molecular-level insights from intensive PM2.5 sampling on winter hazy days - M. Kang; M. Kang; M. Bao; M. Bao; M. Bao; W. Song; W. Song; A. Abulimiti; A. Abulimiti; C. Wu; C. Wu; F. Cao; et al. (Atmospheric Chemistry and Physics)
Reports on the molecular-level characterization of primary and secondary constituents in PM2.5 at high temporal resolution, particularly during haze events, are still limited. This study employed comprehensive analytical methods to examine the molecular composition and source contributions of PM2.5, with samples collected approximately every 2 h during hazy winter days. Results show that organic matter was the predominant species, followed by nitrate (NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="8c72af1edd6d67ed562efcaf5163d22b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-73-2025-ie00001.svg" width="9pt" height="16pt" src="acp-25-73-2025-ie00001.png"/></svg:svg>). Radiocarbon analysis of carbonaceous fractions reveals that fossil fuels account for 61 %–82 % of water-soluble organic carbon (WSOC), likely resulting from increased fossil fuel consumption during cold heating months. Interestingly, the contribution of non-fossil sources to WSOC enhanced with worsening haze pollution, coinciding with significantly intensified biomass burning (BB). BB was identified as the largest contributor to organic carbon (OC) in both concentration and proportion, due to intensive BB emissions in the surrounding areas, especially on heavily polluted days. For secondary sources, naphthalene-derived secondary organic carbon (SOC) contributed more to OC in PM2.5 (0.27 %–2.46 %) compared to biogenic SOC (0.05 %–1.10 %), suggesting anthropogenic volatile organic compounds (VOCs), such as those from fossil fuel and biomass combustion, play a major role in SOC formation in urban aerosols during winter. In addition to promoting secondary aerosol formation, BB could also enhance emissions from other sources, as evidenced by significant correlations between BB tracers and various other source tracers. These findings highlight the significant role of BB in contributing to heavy winter haze.